Implikasi Talak Akibat Pengaruh Sihir terhadap Status Pernikahan: Implications of Divorce Due to the Influence of Magic on Marital Status - Muhammad Istiqamah; Muhammad, Muhammad; Ronny Mahmuddin; Khaerunnisa Karunia (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This study aims to determine the legal implications of divorce due to the influence of magic on marital status and how to prove it. The research method used is library research by collecting and analyzing data from various literature. The phenomenon of divorce due to the influence of magic is explained in the Quran, hadiths, and opinions of scholars. The results show that if a husband divorces his wife while under the influence of magic which causes him to lose consciousness and sanity, then the divorce is invalid. However, if the magic only prevents him from doing something else, and he is aware when issuing the divorce, then the divorce is legal. To prove whether a husband's sanity is impaired due to magic, the husband must provide evidence that he has symptoms of being affected by magic which causes him to lose sanity. If the wife suspects her husband divorced her while insane due to magic, the burden of proof is on the wife to prove the husband has symptoms of magic which causes him to lose sanity and divorce her unconsciously. In conclusion, a divorce due to uncontrolled magical influence is invalid, while one done consciously is legal. The burden of proof lies with the husband or wife, depending on who claims insanity due to magic.